User requirements assessment of the community health information tracking system implications for digital preservation - Trinidad, Daryll O., 1994-; Olgado, Benedict S. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2015)
Electronic Medical Records hold highly important and confidential information. Thus, it is necessary that these records are kept in a trustworthy repository set in a sustainable environment to ensure its preservation for the long term. This study focused on the assessment of the organizational infrastructure of healthcare units equipped with Community Health Information Tracking System (CHITS) using the Trustworthy Digital Repository Checklist as tool to evaluate its current work processes and its readiness on the long-term preservation of Electronic Medical Records.
A questionnaire patterned to the TDR Checklist was sent to the respondents. One respondent in each of the six districts of Quezon City was chosen in an effort to look into the organizational infrastructure of CHITS on an end-user level. Out of the six respondents, five are Medical Officers III who work as physicians and heads of the administration, and one is a Nurse III who temporarily acts as the head of the health center while the position of Medical Officer III is vacant. The Quezon City Health Department was also asked to provide an overview of the current status of the use of CHITS in the HCUs. Of the two respondents from QCHD, one respondent is a Health Officer and the Division Chief (Field Operation) who is tasked to oversee the entire CHITS project and act as a coordinator with the UP Manila National TeleHealth Center. The other respondent is the designated IT Officer for the Department who is in charge with troubleshooting and IT support for CHITS.
The QCHD is able to comply with 10 out of 25 (40%) of the identified Organizational Infrastructure criteria and 7 out of 8 (87.5%) Technical Infrastructure and Security Risk Management criteria in the TDR Checklist. On the other hand, 9 out of 25 (36%) of the identified Organizational Infrastructure criteria was fulfilled by at least half of the six HCUs, and 5 out of 8 (62.5%) Technical Infrastructure and Security Risk Management criteria were fulfilled by all of the respondent.
Undergraduate thesis(B.L.I.S.)--University of the Philippines, Diliman
Keywords: Medical records -- Philippines -- Data processing; Records retention -- Philippines -- Quezon City; Electronic data processing documentation -- Philippines -- Quezon City